Report of the Proceedings of the Third Council Meeting of ASEAN Chambers of Commerce and Industry Held at Dewan Tunku Abdul Rahman, Kuala Lumpur, Malaysia (The ASEAN Chambers of Commerce and Industry, 1975)
19 p